LOKALISASI ORE - Ratnasari, Lucia (MATEMATIKA, 2006)
﻿﻿Let  be a noncommutative ring and  be a multiplicative subset of . The right (left) ring of quotients does not exist for every. A necessary condition of existence right (left) ring of quotients is  right (left) permutable and right (left) reversible. A multiplication subset  is called a right (left) denominator if it is right (left) permutable and right (left) reversible. The ring  has a right (left) ring of quotients with respect to  if and only if  is a right (left) denominator set. We can construct right (left) ring of quotients by using Ore localizations.